Association of Antibiotic Treatment With Outcomes in Patients Hospitalized for an Asthma Exacerbation Treated With Systemic Corticosteroids - Stefan, Mihaela S. (JAMA Intern Med, 2019)
IMPORTANCE: Although professional society guidelines discourage use of empirical antibiotics in the treatment of asthma exacerbation, high antibiotic prescribing rates have been recorded in the United States and elsewhere. OBJECTIVE: To determine the association of antibiotic treatment with outcomes among patients hospitalized for asthma and treated with corticosteroids. DESIGN, SETTING, AND PARTICIPANTS: Retrospective cohort study of data of 19 811 adults hospitalized for asthma exacerbation and treated with systemic corticosteroids in 542 US acute care hospitals from January 1, 2015, through December 31, 2016. EXPOSURES: Early antibiotic treatment, defined as an treatment with an antibiotic initiated during the first 2 days of hospitalization and prescribed for a minimum of 2 days. MAIN OUTCOMES AND MEASURES: The primary outcome measure was hospital length of stay. Other measures were treatment failure (initiation of mechanical ventilation, transfer to the intensive care unit after hospital day 2, in-hospital mortality, or readmission for asthma) within 30 days of discharge, hospital costs, and antibiotic-related diarrhea. Multivariable adjustment, propensity score matching, propensity weighting, and instrumental variable analysis were used to assess the association of antibiotic treatment with outcomes. RESULTS: Of the 19 811 patients, the median (interquartile range [IQR]) age was 46 (34-59) years, 14 389 (72.6%) were women, 8771 (44.3%) were white, and Medicare was the primary form of health insurance for 5120 (25.8%). Antibiotics were prescribed for 8788 patients (44.4%). Compared with patients not treated with antibiotics, treated patients were older (median [IQR] age, 48 [36-61] vs 45 [32-57] years), more likely to be white (48.6% vs 40.9%) and smokers (6.6% vs 5.3%), and had a higher number of comorbidities (eg, congestive heart failure, 6.2% vs 5.8%). Those treated with antibiotics had a significantly longer hospital stay (median [IQR], 4 [3-5] vs 3 [2-4] days) and a similar rate of treatment failure (5.4% vs 5.8%). In propensity score–matched analysis, receipt of antibiotics was associated with a 29% longer hospital stay (length of stay ratio, 1.29; 95% CI, 1.27-1.31) and higher cost of hospitalization (median [IQR] cost, $4776 [$3219-$7373] vs $3641 [$2346-$5942]) but with no difference in the risk of treatment failure (propensity score–matched OR, 0.95; 95% CI, 0.82-1.11). Multivariable adjustment, propensity score weighting, and instrumental variable analysis as well as several sensitivity analyses yielded similar results. CONCLUSIONS AND RELEVANCE: Antibiotic therapy may be associated with a longer hospital length of stay, higher hospital cost, and similar risk of treatment failure. These results highlight the need to reduce inappropriate antibiotic prescribing among patients hospitalized for asthma.